Migration Processes in Contemporary Estonia - Włodarska-Frykowska, Agata (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
This article examines migration trends in contemporary Estonia, focusing on migrant movements, legal regulations applying to migrants and national policies dealing with migration. Estonia is a multi-ethnic country in which both immigration and emigration occur on a considerable scale; consequently, understanding migration patterns and trends is particularly important. Historical factors have influenced Estonian society in a way which has necessitated the implementation of integration programmes and strategies aimed at social consolidation. The article features an analysis of the main changes in migration movements in Estonia since it gained independence and presents contemporary tendencies.